Therapeutic Adherence in Hypertensive Patients of the Guanabacoa Julio Antonio Mella University Polyclinic - Addys Díaz Piñera; Armando Rodríguez Salvá; Milenia León Sánchez; Lisbeth Fernández González; Armando Humberto Seuc Jo; Nelsy Álvarez Mesa (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Background: low adherence to pharmacological treatment is considered a Public Health problem. Social, economic and cultural determinants play an essential role in its origin. Objective: to investigate the level of adherence to pharmacological treatment in a subsample of hypertensive people from the Julio Antonio Mella University Polyclinic in the Guanabacoa municipality and to identify the main factors that may be interfering in this process. Methods: a descriptive cross-sectional study was carried out in the previously mentioned area between September and December 2019. Simple random sampling was used. 337 hypertensive people older than 35 years were studied. The variables studied were: sociodemographic (age, sex, skin color, occupation, education, household composition or cohabitation) and variables related to patient care: need for care, follow-up, blood pressure measurement, treatment prescription pharmacological and non-pharmacological and adherence. Categorical variables were presented as frequencies and percentages. Results: adherence was 69.4 %, it was related to feeling the need for care (p≤0.01), being controlled (p≤0.05) and being older than 65 years (p≤0.04). People with a history of cardiac events and stroke followed to treatment. The rest of the sociodemographic variables were not related, nor the follow-up consultation and blood pressure measurement in the last year. Conclusions: achieving adequate therapeutic adherence is a complex process, influencing both individual and organizational aspects. The unavailability of medications in the pharmacy, forgetting to take them and at the established times were the main barriers referred to; these must be taken into account to have a favorable impact on patient control. It is important to implement strategies to improve the level of adherence and knowledge of patients about their disease.